2023
DOI: 10.3389/fimmu.2023.1094378
|View full text |Cite
|
Sign up to set email alerts
|

Decreased monocyte-to-lymphocyte ratio was associated with satisfied outcomes of first-line PD-1 inhibitors plus chemotherapy in stage IIIB-IV non-small cell lung cancer

Abstract: ObjectivesImmune-checkpoint inhibitors (ICIs) combined with chemotherapy are more widely used than monotherapy and have shown better survival in patients with advanced non-small cell lung cancer (NSCLC) without oncogenic driver alterations. The monocyte-to-lymphocyte ratio (MLR) might predict the treatment outcomes of ICI therapy in advanced NSCLC patients but has not yet been investigated. In addition, the cutoff of MLR is controversial. Therefore, the present study aimed to explore the associations between c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…While our meta-analysis only considered baseline NLR as an indicator for predicting irAEs, some other studies have also investigated the predictive value of dynamic or post-treatment NLR ( 13 , 33 , 38 , 46 , 57 , 60 , 63 ). However, these studies have not found dynamic or post-treatment NLR to be a better predictor than baseline NLR, although more recent studies have focused on studying dynamic NLR as an independent predictor.…”
Section: Discussionmentioning
confidence: 99%
“…While our meta-analysis only considered baseline NLR as an indicator for predicting irAEs, some other studies have also investigated the predictive value of dynamic or post-treatment NLR ( 13 , 33 , 38 , 46 , 57 , 60 , 63 ). However, these studies have not found dynamic or post-treatment NLR to be a better predictor than baseline NLR, although more recent studies have focused on studying dynamic NLR as an independent predictor.…”
Section: Discussionmentioning
confidence: 99%
“…At present, many studies have reported the relationship between various clinicopathological parameters in NSCLC and the therapeutic efficacy of ICIs ( 41 , 42 ). However, few studies have been performed to assess the prediction of PD-L1 expression before therapy ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…We manually retrieved patients’ laboratory data measured one week before neoadjuvant treatment from the electronic medical record system of SYSUCC, including the counts of neutrophils (10 9 /L, N), monocytes (10 9 /L, M), platelets (10 9 /L, P), lymphocytes (10 9 /L, L), and serum albumin concentrations (10 5 /L, A). The specific serum inflammation indexes were calculated as follows: PIV = N*M*P/, 18 , 19 NLR = N/L, 20 MLR = M/L, 21 PLR = P/L, 20 platelet–albumin ratio (PAR) = P/A, 22 systemic immune inflammation index (SII) = P*NLR, 23 PNI = A+5*L, 24 systemic inflammation response index (SIRI) = N*ML. 25 , 26 According to the cutoff value determined by the median value, continuous serum inflammation index parameters were classified as categorical variables (high vs low), namely, PIV (371.97), NLR (2.51), MLR (0.26), PLR (157.50), PAR (6.70), SII (389.55), PNI (52.33), and SIRI (1.35).…”
Section: Methodsmentioning
confidence: 99%